Training elementary school teachers-to-be at Computer Science lessons to evaluate e-tools - Nadiia V. Olefirenko; Ilona I. Kostikova; Nataliia O. Ponomarova; Kateryna O. Lebedieva; Vira M. Andriievska; Andrey V. Pikilnyak (Academy of Cognitive and Natural Sciences, 2020)
The study purpose is to develop methodological support for students' training for evaluation e-tools for young learners and to check its effectiveness experimentally. The module "Expert evaluation of the quality of e-tools for young learners" is offered for teachers-to-be. The determination of the weighting factor of each criterion by expert evaluations was organized. Educational principles, correlation e-tool content with the curriculum, interactivity, multimedia, assistance system, ergonomic requirements are mentioned. On the basis of the criterion rank, the significance of each criterion was calculated. The indicators to determine the level of preliminary expert evaluations of e-tools are proposed. The results are calculated with nonparametric methods of mathematical statistics, in particular, Pearson's criterion χ2. The conclusion is the expert evaluation has different activity stages, gradually becoming a common phenomenon. Training teachers-to-be for e-tool expert evaluation at Computer Science, Mathematics, English is a complex process.